In-vivo biotransformation of citrus functional components and their effects on health. Issue 5 (9th March 2021) - Karn, Abhisek; Zhao, Chengying; Yang, Feilong; Cui, Jiefen; Gao, Zili; Wang, Minqi; Wang, Fengzhong; Xiao, Hang; Zheng, Jinkai
Abstract: Citrus, one of the most popular fruits worldwide, contains various functional components, including flavonoids, dietary fibers (DFs), essential oils (EOs), synephrines, limonoids, and carotenoids. The functional components of citrus attract special attention due to their health-promoting effects. Food components undergo complex biotransformation by host itself and the gut microbiota after oral intake, which alters their bioaccessibility, bioavailability, and bioactivity in the host body. To better understand the health effects of citrus fruits, it is important to understand the in-vivo biotransformation of citrus functional components. We reviewed the biotransformation of citrus functional components (flavonoids, DFs, EOs, synephrines, limonoids, and carotenoids) in the body from their intake to excretion. In addition, we described the importance of biotransformation in terms of health effects. This review would facilitate mechanistic understanding of the health-promoting effect of citrus and its functional components, and also provide guidance for the development of health-promoting foods based on citrus and its functional components.